When women disappear from the labour market: occupational status of Dutch women at marriage in a modernizing society, 1865-1922 - Schulz, Wiebke; Maas, Ineke; van Leeuwen, Marco H.D. (The history of the family, 2014)
Between 1865 and 1922 the labour force participation of women at marriage dropped considerably in the Netherlands. At the same time, girls' educational participation increased and egalitarian gender values started to spread. We expect these developments to have affected the occupational status of those women who stayed in the labour market. Using a large dataset of Dutch marriages and municipal-level information on female labour force participation, educational participation, and an indicator of gender values, we show that women's status dropped until around 1885 and then started to rise. The retreat of women from the labour market coincided with a decline in the status of the women who remained, whereas, especially after 1900, the increasing educational participation of girls and the dissemination of egalitarian gender values counteracted this trend by causing women's status to rise.